(untitled) (Docentes 2.0 Journal, 2024)
The educational field requires co-responsibility in an act supported from within the family that generates the purposeful construction of knowledge, with actions based on ethical and moral values ??that consolidate the metacognition of adolescents. Therefore, the general objective was to determine the relationship between family co-responsibility and the improvement of the metacognitive performance of adolescents in a fiscal Educational Unit of Manabí, in the Republic of Ecuador, 2023. The research that was based on the systematic method, with the positivist paradigm, focused on the quantitative approach, framed in the non-experimental design, being of a basic type with a cross-sectional section, had a population of 64 adolescents, the same ones who made up the sample, this being obtained under a simple sampling at the convenience of the researcher. In addition, it required using the survey as a technique and the questionnaires as instruments duly validated by experts and subjected to a reliability test using Cronbach’s Alpha. The data analysis required statistics using the SPSS version 29.0 application, whose correlation results established that adolescents present a low level of family co-responsibility, as well as in metacognitive performance, with 45.31% and 46.87%, respectively, leaving a significant relationship measure as an answer to the question posed, concluding with the existence of a relationship between family co-responsibility and the improvement of metacognitive performance.